Hepatoprotective Effect of Jianpi Huoxue Formula on Nonalcoholic Fatty Liver Disease Induced by Methionine-Choline-Deficient Diet in Rat. (1st July 2019) - Feng, Yu; Chen, Yan; Yang, Binrui; Lan, Qingping; Wang, Tao; Cui, Guozhen; Ren, Zhitao; Choi, I. Cheong; Leung, George Pak-Heng; Yan, Fenggen; Chen, Dacan; Yu, Hon Ho; et al.
Abstract : In parallel with the prevalence metabolic syndrome, nonalcoholic fatty liver disease (NAFLD) has become the most common chronic liver disease in most countries. It features a constellation of simple steatosis, nonalcoholic steatohepatitis (NASH), fibrosis, cirrhosis, and even hepatocellular carcinoma. There are no approved drugs for effective management of NAFLD and NASH. Jianpi Huoxue formula (JPHX) mainly consists of Atractylodes macrocephal (Baizhu), Salvia miltiorrhiza ( Danshen ), Rasux Paeonia Alba ( Baishao ), Rhizoma Alismatis ( Zexie ), and Fructus Schisandrae Chinensis ( Wuweizi ), which may have beneficial effects on NAFLD. The aim of the study was to identify the effect of JPHX on NAFLD . A NAFLD model was induced by methionine-choline-deficient food (MCD) in Wistar rats and orally administered with simultaneous JPHX, once a day for 8 weeks. Hepatocellular injury, lipid profile, inflammation, fibrosis, and apoptosis were evaluated. The results showed that JPHX significantly decreased the abnormal serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels compared with the MCD model (P<0.05). Furthermore, JPHX protected MCD diet-fed rats from accumulation of hepatic triglycerides (TG) and total cholesterol (TC). Histological examination demonstrated that JPHX noticeably normalized the NAFLD activity score (NAS). Moreover, JPHX ameliorated liver inflammation by decreasing TNF- α levels and reduced collagen and matrix metalloproteinases in MCD diet-fed rats. In addition, JPHX prevented rats from MCD-induced cellular apoptosis, as suggested by TUNEL staining, and suppressed the activation of caspase 3 and 7 proteins. JPHX also inhibited the phosphorylation of JNK. In conclusion, JPHX exhibited a hepatoprotective effect against NAFLD in an MCD experimental model.